Tess of the d'Urbervilles - Hardy, Thomas, 1840-1928. (London : Harper Collins, 2010)
Tess of the d'Urbervilles is a harrowing critique of social class and the powerlessness of women. Tess, a beautiful young woman, is pushed on her rich "relatives" by her grasping father. When the young Lord does with her as he likes, Tess's whole life falls into ruins from which she attempts to free herself. The novel met with mixed reviews upon publication, because it challenged the precepts of society. It is now considered a classic of English literature.
Keywords: Triangles (Interpersonal relations) -- Fiction; Children of the rich -- Fiction; Children of clergy -- Fiction; Women household employees -- Fiction; Women murderers -- Fiction; Poor families -- Fiction; Wessex (England) -- Fiction; Pastoral fiction; Didactic fiction